Thermal Gradient Pattern of Shallow Pitting Via Active Thermography – Hot Water and Steam. - Ismon, Maznan bin; Ismail, Al Emran bin; Zainulabidin, Muhd. Hafeez bin; Mat Noor, Fazimah binti; Abd Wahab, Hanani binti; Mohamad, Zaleha binti; Madlan, Mohd Amran bin (International Journal of Integrated Engineering, 2018)
Pipelines are extensively used worldwide to transport water, oil and gas. Wall thinning or pits can be produced in the internal of the pipe after being used for a certain period of the time due to some factor such as erosion-corrosion and pitting corrosion. This problem concern lots of company in this industry because leakage of pipe cause system failure, hazard at workplace and increase of maintenance cost. This study detected internal wide and shallow pitting of pipe using infrared thermography. For the test specimen, ASTM A106 Grade B carbon steel pipe was drill with five similar size defects shallow pitting of different depth. The result found that all defects appear at temperature 90°C, while only four defects appear at 70°C and 80°C. This is due to the higher the temperature introduced into the pipe, the higher the temperature gradient. Temperature 90°C produce the shortest time for the spot to appear while temperature 70°C take the longest time. Image analysis software, ImageJ measured that the size of defect in the thermogram appear 146% to 222% larger than the actual size.